A Critique of the Boasian Paradigm for Northwest Coast Art - Halpin, Marjorie (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1994)
Halpin challenges Franz Boas’s representationist reading of Northwest Coast art, and the hegemonic discourse that he initiated. In contrast to the Boasian rule-based paradigm, and with specific reference to Tsimshian-speaking peoples, she argues that Northwest Coast Native art is ambiguous, imaginative, unstable, poetic, endlessly variable, changing, and productive of the new, the unexpected. Of paramount importance in her analysis is the relationship between crest art and the oral tradition that still gives it meaning, a relationship that Boas did not understand.